Relevansi Kompetensi Mata Pelajaran Produktif dengan Kompetensi Industri Program Keahlian Teknik Kendaraan Ringan - Soepraptono Soepraptono; Nizwardi Jalinus; Fahmi Rizal (Universitas Negeri Padang, 2019)
This research is included in the type of qualitative research. This study aims to determine the relevance of productive subject competencies with the industry competency of the Vocational Light Vehicle Engineering Skills program. Overall competencies learned by students in schools are in accordance with the syllabus contained in the light vehicle engineering expertise curriculum that teaches introductory theories for skills lessons, expected attitudes of discipline, responsibility, honesty and high work ethic. Competency of productive subjects of light vehicle engineering in schools is almost all needed in the industrial world. This can be seen from the average results of all competency categories of 89.67%. Infrastructure facilities must always be improved to always keep abreast of technology, so teachers always develop their abilities with training, training and internships in industry. In order to develop students' competencies Learning practices in schools are carried out using standard operating procedures.